The Design and Validity of STEM-EDP-gamification Worksheet: Ways to Improve Students' Perception of Their STEM Skills and Motivation - Khoiriyah, Riva; Sukriadi, Sukriadi; Haerani, Rosita Putri Rahmi; Suhartini, Erna; Efwinda, Shelly (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This article discusses the design and validity of STEM gamification worksheets as a means to improve students' perceptions of skills and motivation in STEM learning. This study encourages student motivation and engagement in STEM learning more engagingly and innovatively. This study uses a mixed-method approach with an Educational Design Research (EDR) approach. The EDR method consists of three phases: the first phase is analysis and exploration, the second phase is design and construction, and the third phase is evaluation and reflection. The STEM gamification worksheet was designed using the EDP (Engineering Design Process) learning model designed for four meetings. The worksheet obtained an average assessment for all aspects, namely the content and feasibility aspects of the STEM gamification-based worksheet product of 89.3% which is included in the